The role of informal digital learning of English and a high-stakes English test on perceptions of English as an international language - Lee, Ju Seong (Australasian Journal of Educational Technology, 2020)
This study investigated the relationship among informal digital learning of English (IDLE) practice, a high-stakes English test, English productive skills, and perceptions of English as an international language (EIL). Eighty-nine English as a foreign language (EFL) undergraduate students across three South Korean cities participated in the study. The participants submitted their scores in the Test of English for International Communication (TOEIC, South Korea’s most popular high-stakes English test), took English speaking and productive vocabulary-level tests, and completed surveys that measured the frequency of their IDLE activities and EIL perceptions. Results of the hierarchical multiple regression analyses showed that IDLE practice and TOEIC scores were significant predictors of EIL perceptions. The structural equation modelling analysis further revealed that IDLE practice partially mediated the relationship between TOEIC scores and EIL perceptions. This indicates that students with higher TOEIC scores tended to practise IDLE activities more frequently, which enabled them to experience diverse accents and users of English and, in turn, help increase their EIL perceptions. It also suggests that more proficient EFL speakers may not necessarily become competent EIL users. These findings are discussed with consideration of South Korea’s socio-educational contexts, followed by pedagogical implications for English language educators and test developers.